Biogenic Amines in Insect Antennae - Zhukovskaya, Marianna I.; Polyanovsky, Andrey D. (Frontiers in Systems Neuroscience, 2017)
Insect antenna is a multisensory organ, each modality of which can be modulated by biogenic amines. Octopamine and its metabolic precursor tyramine affect activity of antennal olfactory receptor neurons. There is some evidence that dopamine modulates gustatory neurons. Serotonin can serve as a neurotransmitter in some afferent mechanosensory neurons and both as a neurotransmitter and neurohormone in efferent fibers targeted at the antennal vessel and mechanosensory organs. As a neurohormone, serotonin affects the generation of the transepithelial potential by sensillar accessory cells. Other possible targets of biogenic amines in insect antennae are hygro- and thermosensory neurons and epithelial cells. We suggest that the insect antenna is partially autonomous in the sense that biologically active substances entering its hemolymph may exert their effects and be cleared from this compartment without affecting other body parts.